2021
DOI: 10.1371/journal.pone.0255144
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes increases the risk of COVID-19 in an altitude dependent manner: An analysis of 1,280,806 Mexican patients

Abstract: Aims The objective of this study is to analyze how the impact of Diabetes Mellitus [DM] in patients with COVID-19 varies according to altitudinal gradient. Methods We obtained 1,280,806 records from adult patients with COVID-19 and DM to analyze the probability of COVID-19, development of COVID-19 pneumonia, hospitalization, intubation, admission to the Intensive Care Unit [ICU] and case-fatality rates [CFR]. Variables were controlled by age, sex and altitude of residence to calculate adjusted prevalence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 68 publications
1
18
0
2
Order By: Relevance
“…It has been reported that the prognosis is worse in patients with type 2 DM who have metabolic syndrome (MetS) components at the onset of the COVID-19 infection. 16 …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the prognosis is worse in patients with type 2 DM who have metabolic syndrome (MetS) components at the onset of the COVID-19 infection. 16 …”
Section: Discussionmentioning
confidence: 99%
“…The presence of DM was identified in 12.97% of the total number of records. According to the findings, diabetes patients were more likely to contract COVID-19 and develop pneumonia [57] . Liu Z et al carried out a retrospective observational study for a large sample group (1880 patients).…”
Section: What Effect Does Diabetes Mellitus Have On Covid-19 and Vice...mentioning
confidence: 97%
“…COVID-19 and diabetes mellitus are correlated in a bidirectional manner, according to research[ 26 ]. Diabetes mellitus is a common comorbidity among COVID-19 patients[ 27 ]. Diabetes exacerbates disease severity and mortality, increasing the probability of infection with SARS-CoV-2[ 28 ].…”
Section: Discussionmentioning
confidence: 99%